Health Care Financing in Nigeria: Prospects and Challenges - Obansa, S. A. J.; Orimisan, Akinnagbe (Richtmann Publishing, 2013)
Fifty years after independence, Nigeria is still struggling with the provision of basic health services for its teeming population,now estimated at over 150million. The health care sector is still a labour-intensive handicraft industry, in spite of advances intechnology, and health care provision has now become more complicated than in the past. Infant and under-five mortality ratesare near the highest in the world, and maternal mortality is extremely high. It has the second largest number of people infectedwith HIV/AIDS in the world only next to South Africa and in 2008, between 3million and 3.5million people were estimated to beliving with HIV/AIDS. Nigeria has the fourth highest number of TB cases in the world, with a 2004 estimate of 293 new casesper 100,000 population and 546 per 100,000 total cases. The reasons for a dysfunctional health system include: gross inadequate infrastructural support, electricity, potable water and diagnostic laboratories, very low per capita health spending,high out-of-pocket expenditure by citizens, and a total absence of a community-based integrated system for diseaseprevention, surveillance and treatment amongst others. Some strategies to tackle health sector challenges in Nigeria mayinclude improved access to primary healthcare; strategic and purposeful leadership in health delivery services; increasingfunding to the health sector; amongst others.